Widely tunable intersubband energy spacing of self-assembled InAs/GaAs quantum dots due to interface intermixing - Wang, X. C. (2013)
In this article, we showed the significant reduction of the energy spacing between ground state and excited state emissions from InAs/GaAs quantum dots(QDs) due to interface interdiffusion induced by thermal treatment. In addition, the strong narrowing of the luminescencelinewidth of the ground state and excited state emissions from the InAs dot layers for the annealed samples indicates an improvement of the size distribution of the QDs. Large blueshift of the energy positions of both emissions was also observed. High resolution x-ray diffraction experiments give strong evidence of the interface atom interdiffusion in the annealed samples. This work shows the ability to tune the wavelength for applications like infrared detectors and lasers based on intrasubband transitions of self-assembledQDs.